Response to Letter: Enhancing Adolescent Nutrition Knowledge Through Digital Innovation: Evaluating the Effectiveness of E-Pocket Books in Reducing Obesity - Hastuti, Puput Tri; Utami, Siti Budi; Rialihanto, Muhammad Primiaji; Susilo, Joko; Attawet, Jutharat; Siswati, Tri (Health Dynamics, 2025)
Not mandatory